(untitled) (Research, Society and Development, 2020)
Objective: The use of natural products for diverse affections treatments is something aged, described since the man’s cradle, which made use of plants for wounds and natural disorders treatments. That said, the assignment objective is to expose the presentation of an experience report in case of an inflammatory process of bacteria origin due an acne treated with melaleuca essential oil associated with the photo dynamics therapy. Methods: For such, the specific spot to be worked on was sanitized with a cleaning solution and after it was hydrated with an invigorating solution. It was used on the spot 20 µL of melaleuca (Melaleuca aternifólia) essential oil and also it was performed a circular massage to spread the product. Over the spot was fell upon a blue intensity light (± 550nm) focusing on it. Results: After 5 minutes exhibition, edema decreased and pore closure was observed due to an absence of intense fushing, going intense to slight., edema decreased and pore closure. In brief, it is possible to say that the malaleuca essential oil association with application of photo dynamic therapy has the remedial potencial on facing inflammatory and infectious processes caused by acne. Conclusion: Lastly, the propagation of cases reports are of crucial importance, since that comparisons with the literature can lend to new therapies alternatives.